2016
DOI: 10.1002/hed.24301
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic endonasal study of the cavernous sinus and quadrangular space: Anatomic relationships

Abstract: The trajectory of the internal carotid artery (ICA) significantly impacts the quadrangular space area and may be a potential parameter for defining the feasibility of this corridor. © 2016 Wiley Periodicals, Inc. Head Neck 38: E1680-E1687, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…First, duplicates (n = 89) and non-English abstracts (n = 25) were removed; thereafter, 157 abstracts were screened for relevance resulting in the full-text evaluation of 112 articles. Subsequently, 75 articles were identified for our qualitative synthesis and included case reports (n = 21) , cadaveric studies (n = 32) [3,6,7,10,13,, clinical articles (n = 16) [2,5,8,9,16,[61][62][63][64][65][66][67][68][69][70][71], review of the literatures (n = 3) [72][73][74], as well as technical notes (n = 2) [75,76] and a radiological manuscript (n = 1) [77]. These outlined articles were published between February 1978 and November 2018.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, duplicates (n = 89) and non-English abstracts (n = 25) were removed; thereafter, 157 abstracts were screened for relevance resulting in the full-text evaluation of 112 articles. Subsequently, 75 articles were identified for our qualitative synthesis and included case reports (n = 21) , cadaveric studies (n = 32) [3,6,7,10,13,, clinical articles (n = 16) [2,5,8,9,16,[61][62][63][64][65][66][67][68][69][70][71], review of the literatures (n = 3) [72][73][74], as well as technical notes (n = 2) [75,76] and a radiological manuscript (n = 1) [77]. These outlined articles were published between February 1978 and November 2018.…”
Section: Resultsmentioning
confidence: 99%
“…A quadrangular space delineated by the ICA medially and inferiorly, the V2 nerve laterally, which is superolateral to the ICA [7], and the abducens nerve with the CS superiorly, provides access to Meckel's cave [79]. The ICA course should be carefully studied to define the feasibility of this approach [13] and avoid injury while drilling.…”
Section: Transpterygoid Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The anterior genu and anterior vertical segment are referred to as the lacerum segment by Bouthillier et al 1 Many studies have reported how to find the anterior end of the VC and follow the VN toward the lacerum segment of the petrous horizontal ICA. 3,5,10,15,16,19 The VC is a useful landmark to reach the lacerum segment of the ICA at its transition from the horizontal petrous segment to its vertical paraclival segment, especially in patients with poor sphenoid sinus pneumatization or those with recurrent pathology in whom the conventional surgical anatomy may be distorted. Moreover, exposure of the VN allows further exposure of the pterygoid base and lateral wall of the sphenoid sinus, as part of the transpterygoid approach.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many publications focus on different anatomical landmarks of the anterior end of the VC and how the endonasal transpterygoid approach may be performed safely. [3][4][5]16,17,19,23 However, the literature is lacking a thorough anatomical description of the posterior and inferior limits of the endonasal transpterygoid avenue. Although the identification of the VN in the proximal aspect of its canal may permit us to safely identify the anterior genu of the ICA, the endoscopic anatomy of the most inferior and posterior area surrounding the ICA in this region-that is, the deepest and most posterior limit of the endoscopic endonasal transpterygoid route-has not been well documented.…”
mentioning
confidence: 99%